Spatial Distribution and Temporal Variability of Ammonium-Nitrogen, Phosphorus, and Potassium in a Rice Field in Corrientes, Argentina - Luis Alberto Morales; Eva Vidal Vázquez; Jorge Paz-Ferreiro (The Scientific World Journal)
Proper and effective management of soil nutrients requires assessment of their variability at the field scale. We compare the effects of lime amendment rate on the spatial variability of three macronutrient forms (NH4+-N, Olsen P, and Mehlich-1 K) in a paddy soil at three different dates during the growth period of a rice crop. The field work was carried out near Corrientes, Argentina. Lime treatments were 0, 625, and 1250 kg ha−1 dolomite, and each liming dose was applied to a 1.7 ha field. Ninety-three soil samples per treatment were first collected in aerobic conditions and then two more times after flooding, at bunch formation and flowering. Soil NH4+-N increased along time, whereas P was highest at bunch formation and K steadily decreased along the rice growth period. Dolomite addition increased macronutrient availability at the first and second samplings, but its effects at the third sampling depended on the element. The three soil nutrients analyzed displayed strong patterns of spatial dependence for the three lime treatments and at the three periods studied. The areas with relative high or low macronutrient concentrations within each field were not stable throughout the rice growth period. Seasonality in the spatial distribution of macronutrients may be of agronomic value for site specific management.